2012
DOI: 10.1007/s11365-012-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating competing theories of street entrepreneurship: some lessons from a study of street vendors in Bangalore, India

Abstract: Conventionally, street entrepreneurs were either seen as a residue from a premodern era that is gradually disappearing (modernisation theory), or an endeavour into which marginalised populations are driven out of necessity in the absence of alternative ways of securing a livelihood (structuralist theory). In recent years, however, participation in street entrepreneurship has been re-read either as a rational economic choice (neoliberal theory) or as conducted for cultural reasons (post-modern theory). The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 56 publications
3
62
1
5
Order By: Relevance
“…An ongoing stream of literature, mostly grounded in social exchange theory, examines the antecedents of the affiliative OCB. The results of empirical research show that affiliative OCB relates with organizational leadership 4 (Kwan, Lui andYim, 2012, Wang, Law, Hackett, Wang andChen, 2005), supervisor trust building (Deluga, 1994) and procedural justice (Karriker and Williams, 2009;Williams and Gurtoo, 2012). Organizational-and leader-member exchange are two elements that act as mediators of the relationship between these constructs and OCB.…”
Section: Introductionmentioning
confidence: 99%
“…An ongoing stream of literature, mostly grounded in social exchange theory, examines the antecedents of the affiliative OCB. The results of empirical research show that affiliative OCB relates with organizational leadership 4 (Kwan, Lui andYim, 2012, Wang, Law, Hackett, Wang andChen, 2005), supervisor trust building (Deluga, 1994) and procedural justice (Karriker and Williams, 2009;Williams and Gurtoo, 2012). Organizational-and leader-member exchange are two elements that act as mediators of the relationship between these constructs and OCB.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the main reasons includes an increase in income, attractions of entrepreneurship, self-determination and autonomy, family concerns such as balancing career and family and the lack of career advancement. It was found that semi-literate women in developing countries start more businesses than men because of social inequalities they face and their access to other job opportunities (Williams & Gurtoo 2012).…”
Section: Women-owned Informal Businessesmentioning
confidence: 99%
“…Research suggests that this caring attitude manifests in women's leadership style and that goals other than economic growth guide women's businesses. There is a strong belief amongst women that a successful business should give back to the community, thus enforcing the social contribution factor (Williams & Gurtoo 2012).…”
Section: Women-owned Informal Businessesmentioning
confidence: 99%
See 1 more Smart Citation
“…This more positive view has arisen from the recognition that informal entrepreneurship is not universally necessity-driven and often a voluntary choice (Cross, 2000;Franck, 2012;Gërxhani, 2004;Maloney, 2004;Williams, 2009;Williams and Gurtoo, 2012;Williams and Youssef, 2015). The result is the emergence of new theoretical perspectives.…”
Section: Conceptualizations Of Informal Entrepreneurshipmentioning
confidence: 99%